TEACHER’s ACCOMMODATION TO GRADE 10 STUDENTS’ LEARNING STYLE PREFERENCES IN TEACHING ENGLISH AND IMPLICATIONS FOR TEACHING STYLES AND TEXTBOOK ADAPTATION - A CASE STUDY - Nguyen, Thi Thanh (2020)
“Everyone has strengths, but different people have very different strengths” (Dunn and Dunn, 1983). This statement shows not just a common assumption but a great finding which has been proved with numerous studies in language teaching for ages. Every learner is different in the way they learn in terms of needs, motivation, interest, aptitude, etc. Among them, learning style is the factor which a large number of authors have dedicated their research to examine. Although learning styles have been researched exhaustively, little EFL research in general and in the context of Vietnam has been conducted. Involving a group of grade 10 students in Hanoi, Vietnam and their English language teacher into a case study, this paper was expected to identify the students’ learning styles, examine the extent to which the teacher catered for the students’ different learning modalities and how the students evaluated this accommodation. Using questionnaire, interview and observation as the main methods, the research found out that these students had a strong preference for tactile, kinesthetic and auditory but found it hard to learn in individual, group or visual learning styles.